Characteristics of Base Cake Bar With Addition of Moringa Flour (Moringa oleifera) with Various Types of Rice Flour (Red, Black and White): Karakteristik Base Cake Bar dengan Penambahan Tepung Kelor (Moringa oleifera) dengan Variasi Jenis Tepung Beras (Merah, Hitam dan Putih) - Zulfa Nur Zaeni; Nanik Suhartatik; Akhmad Mustofa (Agrobiotek, 2024)
Base cake bars on the market are madse by soy flour mixed with dried fruit and are unusually consumed as snack in the bars. The base cake bars can be made without flour with high gluten. Mocaf is an alternative carbohydrate source as well as a substitute for wheat flours. The use of rice flour and mocaf flour was chosen becaused of the high fiber content in the various types of rice used. Moringa flour is rich in protein, minerals and vitamins. The advantages of adding Moringa flour can improve the quality of the base cake bar, especially fiber. Determining the formulation of the moringa cake bar base with various types of rice flour which has a high fiber content and is preferred by consumers is the aim of this study. This study used a two factor factorial Completely Randomized Design (CRD) with two replications. The factor used are the ratio of rice flour with Moringa leaf flour (95/5, 90/10, 85/15) and various types of rice flour (red, black, white). Chemical and organoleptic analysis of the best rice-moringa base cake bars was the B3K2 treatment (type of white rice with a ratio of rice flour: moringa 90/10) with 5.21% water content, 2.29% ash content, 17.29% fat content, 9.50% protein content, crude fiber 12.83% and 65.71% for carbohydrates. Organoleptic results with, Moringa flavor 2.19, sandy texture 3.15, density 2.49 and overall preference 3.31.